Fundamentals of Entrepreneurship (ENT300) : Indoor Multipurpose studio / Nazirul Naim Abd Khalid … [et al.] - Abd Khalid, Nazirul Naim; Suhaimi, Muhammad Syafiq; Luka, Andrian; Abu Samah, Muhd Sukarno; Abg Drahman, Abg Zakarni Mahsyuri (2013)
Our business name is Indoor Multipurpose studio. The main operation of our business is to provide the best and comfortable studio rental service in town. Our business is located in area of Stutong, Kuching Sarawak. The main reason we choose this place because the location is near with our target market. The business is in form of partnerships, which consists of five partners. Every partner contributes to the certain amount of equity and all partners agree that they are bounding on the agreement and its condition that has formed.